Financial Performance Analysis (Case Study Of PT Astra International Tbk) - Dea Try Ananda; Bahman Effendi; Wagini Wagini (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2026)
Financial performance reflects the development of a company's financial turnover over a specific period. A company's financial performance can be measured using financial ratio analysis. Indicators for determining whether financial performance is categorized as excellent, good, or poor can be based on general industry standards.The purpose of this study is to analyze the financial performance of PT Astra International Tbk.The financial statement analysis technique used is financial ratio analysis. Financial ratio analysis clarifies or provides an overview of the financial condition or position from one period to the next. Ratios used in financial statement analysis to improve financial performance include solvency ratios, liquidity ratios, profitability ratios, and activity ratios. By understanding a company's financial ratios, we can understand the company's condition and thus measure its financial performance.Therefore, the results of calculating the liquidity ratio using industry standards, the current ratio and quick ratio, averaged 2.66 times for the current ratio and 0.85 times for the quick ratio. Based on the results of the financial performance analysis of PT Astra International Tbk conducted using liquidity, solvency, activity, and profitability ratios in 2024, several conclusions can be drawn. Analysis of liquidity ratios (such as the Current Ratio and Quick Ratio) shows that PT Astra International Tbk is in a fairly good liquid condition. These ratios are generally above industry standards, indicating that the company is able to meet its short-term obligations as they fall due. Analysis of solvency ratios (such as the Debt to Equity Ratio and Debt to Asset Ratio) shows that the level of debt use by the company is in the moderate/healthy category. This reflects a strong capital structure and well-managed financial risks, where most of the company's assets are funded by equity rather than debt. Analysis of activity ratios (such as Total Asset Turnover and Inventory Turnover) shows that the company is relatively efficient in utilizing its assets to generate sales. Total Asset Turnover shows a high asset turnover rate, indicating effective asset management in supporting the Company's operational volume. Profitability ratios (such as Return on Assets (ROA) and Return on Equity (ROE)) indicate that the company's performance in generating profits from its assets and equity is very good and efficient. There was a downward trend in ROA and ROE during the analysis period, indicating management's effectiveness in managing the company's resources to generate profits.